(untitled) (Medical Forum Monthly, 2024)
Objective: This study was aimed to find the correlation of BMI with cholesterol and sugar level in adult Place and Duration of Study: This study was carried out in Department of Medicine, Combined Military Hospital (CMH) Quita from 2006 to 2009. Study Design: Prospective observational cross sectional studies Materials and Methods: Individuals with different ages, sex were selected as study population. The cholesterol and fasting blood sugar were measured according to standard protocol. Height in centimeter and weight in kilograms of each individual was recorded and BMI calculated as kg/m2. Physical examination was done for everybody. The SPSS-20 was used for statistical significant analysis. The frequencies of variable and correlation between BMI, heights, weight, sugar and cholesterol were comprehensively analyzed. Results: A total of 2,174 adults, 1,947 (89.56%) male and 227 (10.44%) female were included in study. Age range was between 20 and 55years.The mean age was 38.47±12.66. Mean BMI was 23.57±2.58.Mean cholesterol was4.57±.60. Mean fasting blood sugar (FBS) was 4.67±.75.Mean weight 70.32±9.1 Mean height 172.73±.7.85.The correlation analysis revealed that weight, fasting blood sugar (FBS) and cholesterol had positive correlation with BMI [correlation coefficient of 0.734 (p<0.000), 0.167(p<0.000), 0.164 (p<0.000) respectively and height had negative correlation with BMI [-0.123 (p<0.000). Conclusion: BMI is positively correlated with weight, RBS and cholesterol. The effect of age, sex, exercise and current medical status, this correlation is reduced.